2014
DOI: 10.1096/fj.13-247643
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cannabinoid 1 receptor blockade activates brown adipose tissue and diminishes dyslipidemia and obesity

Abstract: The endocannabinoid system is an important player in energy metabolism by regulating appetite, lipolysis, and energy expenditure. Chronic blockade of the cannabinoid 1 receptor (CB1R) leads to long-term maintenance of weight loss and reduction of dyslipidemia in experimental and human obesity. The molecular mechanism by which CB1R blockade reverses dyslipidemia in obesity has not yet been clarified. In this study, we showed that CB1R blockade with the systemic CB1R blocker rimonabant enhanced whole-body energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 52 publications
(86 reference statements)
1
63
1
4
Order By: Relevance
“…High plasmatic levels of endocannabinoids have been associated with increased cardiometabolic risk, visceral WAT accumulation, and type 2 diabetes in obese patients ( 19 ). Genetic impairment of CB1 receptors selectively in neurons of the brain and sympathetic nervous system (SNS) enhances energy expenditure by the BAT ( 20 ), and very recent evidence suggests an inhibitory role of prejunctional CB1 on brown adipocyte glucose utilization ( 21 ), thermogenesis, and lipid droplet formation ( 22 ). Furthermore, CB1 blockade in Sim1-expressing neurons of the paraventricular nucleus of the hypothalamus enhances energy expenditure during high-fat diet feeding ( 23 ).…”
Section: Experimental Animals and Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…High plasmatic levels of endocannabinoids have been associated with increased cardiometabolic risk, visceral WAT accumulation, and type 2 diabetes in obese patients ( 19 ). Genetic impairment of CB1 receptors selectively in neurons of the brain and sympathetic nervous system (SNS) enhances energy expenditure by the BAT ( 20 ), and very recent evidence suggests an inhibitory role of prejunctional CB1 on brown adipocyte glucose utilization ( 21 ), thermogenesis, and lipid droplet formation ( 22 ). Furthermore, CB1 blockade in Sim1-expressing neurons of the paraventricular nucleus of the hypothalamus enhances energy expenditure during high-fat diet feeding ( 23 ).…”
Section: Experimental Animals and Dietsmentioning
confidence: 99%
“…While there are several examples of reports [summarized in ( 19 )] pointing to an autocrine role of endocannabinoids and CB1 receptors on white adipocytes, also facilitating, among others, their transformation into beige adipocytes ( 25,26 ), evidence for a similar role in brown adipocytes is still scant . Through the use of a peripherally restricted CB1 antagonist in vivo, and of T37i brown adipocyte-like cells in vitro, Boon et al ( 22 ) very recently suggested that some of the above effects of CB1 blockade in the BAT, and in particular the stimulation of uncoupled respiration, may be exerted postjunctionally and directly on brown adipocytes, most likely by enhancing cyclic AMP/PKA signaling induced by ␤ 3-adrenoceptor activation. However, the question of whether exposure to cold, via sympathetic stimulation of ␤ 3-adrenoceptors in brown adipocytes, enhances endocannabinoid levels in BAT has not been tested so far.…”
mentioning
confidence: 99%
“…Upon randomization and at 4-week intervals during treatment, blood samples were collected after a 6-h fast and assayed for levels of TGs, total cholesterol (TC), and free fatty acids (FFA), as described previously (11,12).…”
Section: Determination Of Plasma Parametersmentioning
confidence: 99%
“…Pieces of snap-frozen mouse tissue (~50 mg) or T37i cells (grown in 3.8 cm 2 wells) were lysed, protein was isolated, and Western blots were performed as previously described (11). Primary antibodies and dilutions are listed in Supplementary Table 1.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…These effects were shown to be mediated by both peripheral CB1 (5) and CB1 located in the central nervous system (CNS) (4).…”
mentioning
confidence: 99%